2017
DOI: 10.9775/kvfd.2017.17394
|View full text |Cite
|
Sign up to set email alerts
|

Sütçü İneklerde Ovaryum Kistlerinin Tanısı ve Metabolik Profili Üzerine Bir Çalışma

Abstract: A clinical study was performed to evaluate the diagnostic methods for ovarian cysts (OC), and to determine the metabolic profiles of animals with OC in the region of Mitidja in the North of Algeria. A total of 504 non-pregnant lactating cows were used in this study. Ultrasonography was performed by EXAGO scanner and was combined with assessment of serum P4. Biochemical serum parameters were assayed by spectrophotometry and insulin and cortisol serum measurement was performed by electrochemiluminescence. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The present study found no significant difference in BMI between the case and control groups, although obesity and overweight are established risk factors for FOC. FOCs are among the most common gynecological diseases worldwide, and their prevalence is influenced by lifestyle and nutritional factors, which are also risk factors for other non-communicable diseases [4,13,14]. Given the high prevalence of overweight and obesity among Iranian women of reproductive age [6], it is noteworthy that 20 (50%) case and 23 (57.7%) control participants in our study had a BMI above 24.5 kg/ m 2 .…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The present study found no significant difference in BMI between the case and control groups, although obesity and overweight are established risk factors for FOC. FOCs are among the most common gynecological diseases worldwide, and their prevalence is influenced by lifestyle and nutritional factors, which are also risk factors for other non-communicable diseases [4,13,14]. Given the high prevalence of overweight and obesity among Iranian women of reproductive age [6], it is noteworthy that 20 (50%) case and 23 (57.7%) control participants in our study had a BMI above 24.5 kg/ m 2 .…”
Section: Discussionmentioning
confidence: 67%
“…Women with a higher BMI can produce more estrogen from steroids in adipose tissue, which has a positive effect on LH production and a negative effect on FSH production. Moreover, an increase in LH levels can cause hyperplasia of the ovarian stroma and an increase in androgen production, ultimately leading to the anovulation cycle in women [13]. Therefore, adopting a proper diet and engaging in appropriate physical activity to lose weight improves insulin levels, insulin resistance, and reduces androgenization, leading to improved ovulation.…”
Section: American Journal Of Biomedical Science and Researchmentioning
confidence: 99%
“…The increased vascularization of the superficial cortical stroma in normal older ovaries and in ovaries due to polycystic syndrome could affect the cortical metabolic rate and thus, the survival of the primordial follicles and lead to early follicular growth [25]. Since ovarian cysts in high-performing dairy cows, like the Holstein-Friesian, are also a major factor affecting fertility [28][29][30], these dynamics should be studied more closely. Particular attention should be paid to the spatial distribution of the blood vessels (superficial and deep cortical stroma).…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of cystic ovarian disease was highest in 2 nd parity and was reduced thereafter, as reported by Roberts [13] . Contrarily, Mimoune et al [14] have reported a higher incidence of COD in 3 rd lactation, Hernendez-Ledezma et al [15] was observed that the incidence of cystic ovary increased from 8.4% in primiparous cows to 25.9% in cows of 5 th lactation. In the present study, no cyst was observed beyond 5 th lactation, which was similar to that reported by Bhattacharyya et al [16] .…”
Section: Discussionmentioning
confidence: 99%